Native speakerism (?!): (Re)Considering critical lenses and corresponding implications in the field of English Language Teaching - Nathanael Rudolph (Universitas Katolik Indonesia Atma Jaya, 2019)
Within English language teaching (ELT), critical scholarship has paid ever-increasing attention to identity, experience and (in)equity, and thus to privilege-marginalization: where it comes from, how and why it manifests, who (potentially) experiences it, and what might be done to address inequity in (and potentially beyond) the profession. This dialogue is intertwined with broader attempts in the field to account for the complexity of identity and interaction in settings around the globe. In this article, I discuss how categorical apprehensions of identity, experience and privilege-marginalization, and approaches to (in)equity, have framed discourse within critical scholarship. I then survey how more recent work has called into question many of the critical “assumptions” (Pennycook, 2001) both shaping and shaped by such theory and inquiry. This scholarship contends that critical lenses predicated upon categories of being, while calling attention to idealized nativeness embedded in ELT, fail to account for the contextualized, sociohistorical negotiation of privilege-marginalization within and transcending communities around the globe. Next, in order to contextualize and unpack these divergent lenses, I provide a review of critical dialogue attending to Japan, both in and beyond ELT, noting in conclusion how privilege-marginalization within ELT is intertwined with the sociohistorical negotiation of “selfhood” and “otherness” pertaining both to Japanese society and Japan and “the world beyond.” I close by briefly commenting on future directions for critical scholarship in ELT, and the challenges facing, and yet to be faced by, its stakeholders.